Activation of a procarcinogen to a mutagen by cell-free extracts of anaerobic bacteria - McCoy, Elena C.; Speck, William T.; Rosenkranz, Herbert S. (Mutation Research/Environmental Mutagenesis and Related Subjects, 1977)
The Salmonella mutagenicity assay can be coupled to cell-free preparations derived from anaerobic bacteria ( Clostridium perfringens and Bacteroides fragilis) to activate a procarcinogen to a mutagen. This activity is destroyed by heating and by digestion with pronase and it is sensitive to oxygen. These findings indicate that the Salmonella mutagenicity assay can be adapted to the study of the role of anaerobes in the activation of carcinogens.